Mathematical media literacy in the COVID-19 pandemic and its relation to school mathematics education - Heyd-Metzuyanim, Einat (Educ Stud Math, 2021)
In the first months of 2020, as the COVID-19 pandemic became a top concern worldwide, media coverage became full of information that demands mathematical literacy, or numeracy, to interpret. In this study, we examine the public’s understanding of mathematical notions that are required for understanding the pandemic and predicting its spread. We also explore its correlations with several variables: age group and gender, educational attainment in mathematics, and mathematics identity. To do so, we conducted a cross-sectional survey focusing on mathematical knowledge relevant to the pandemic. The survey was distributed to a representative sample of the Jewish Israeli population (n = 439). Findings showed that participants’ educational attainment in mathematics was positively correlated with their success in the mathematical media literacy tasks. However, even those with high attainment levels did not always perform well. Moreover, the explanatory variable with the strongest relationship to mathematical media literacy was found to be participants’ mathematical identity. These results suggest that school mathematics, especially in its high levels, may prepare adults to understand critical information important for their well-being, such as at a time of global pandemic. However, they also demonstrate that a weak mathematical identity may significantly hinder adults’ engagement with such information. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10649-021-10075-8.